PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING PADA MATERI BUNGA MAJEMUK KELAS XI SMAN 3 PADANG - Penita Ani Karya; Anna Cesaria; Yulia Haryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of technology utilization in developing teaching materials. The aim of this study is to develop an Electronic Student Worksheet (E-LKPD) based on Problem Based Learning (PBL) for compound interest material in Grade XI at SMAN 3 Padang that is valid and practical. The subjects of this research were students of SMAN 3 Padang. This study employed a research and development (R&D) method with the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The instruments used in this research included teacher and student interview analyses using interview guidelines, material analysis on the module using a checklist, student characteristic analysis using a questionnaire, validation analysis by media experts and material experts using questionnaires, and practicality analysis and interviews using questionnaires and interview guidelines to assess the validity and practicality of the E-LKPD. Based on the E-LKPD validity results obtained from the validation by media experts and material experts, a percentage of 91% was achieved, categorized as very valid. The practicality score from the one-to-one trial with teachers was 90%, categorized as very practical, and from the one-to-one trial with students was 93%, also categorized as very practical. In the small group trial conducted with students, the practicality score was 81%, categorized as very practical. Based on these findings, it can be concluded that the E-LKPD based on Problem Based Learning for compound interest material is declared valid and practical.